A scanner-based colorimetric mercuric ion detection using Tween-20-stabilized AuNPs solution in 96-well plates. Issue 11 (19th September 2017) - Poorahong, Sujittra; Niammusik, Anusorn; Chaykleang, Pawinee; Kanatharana, Pproespichaya; Thavarungkul, Panote; Thammakhet-Buranachai, Chongdee
ABSTRACT: This paper reports the development of a sensitive, high-throughput colorimetric method for the detection of trace mercuric ions (Hg 2+ ). The method is based on the binding of the analyte to gold nanoparticles (AuNPs) modified with Tween-20. Tween-20 was used as a nonionic stabilizer to allow a good dispersion of AuNPs in solution. When mercuric ions were added to the solution, they replaced the Tween-20 stabilizer on the surface of the AuNPs due to their stronger binding affinity. This caused the NPs to aggregate and the color of the solution to change from red to blue. The quantitative analysis of Hg 2+ was achieved by plotting the Red Green Blue (RGB) values of the scanned images of the analyte samples in the AuNP solution against concentrations of Hg 2+ . Since the reaction was carried out in 96-well plates, ninety-six samples were analyzed simultaneously, reducing the cost and time of analysis. The experimental parameters optimized were the concentrations of Tween-20 and NaCl, the reactants ratio, and the incubation time. Under the optimum conditions, the calibration plot of the assay was linear over an Hg 2+ concentration range of 0.10–2.00 mg L −1, and the detection limit was 0.050 mg L −1 (S/N  =  3). The selectivity of the technique was high with no significant colorimetric responses to the presence of 100-fold excesses of other metal ions. Quantification was validated with Hg 2+ standard solutions and spiked tap and waste water samples, and the accuracy of the technique was confirmed. The developed technique is simple and cost effective because it requires no complicated instruments, yet the results demonstrate it to be a very powerful technique with the potential to be developed for on-site mercury detection.